Bone Turnover, Bone Mineral Density, and Fracture Risk in Acromegaly: A Meta-Analysis - Mazziotti, Gherardo; Biagioli, Elena; Maffezzoni, Filippo; Spinello, Maurizio; Serra, Vincenza; Maroldi, Roberto; Floriani, Irene; Giustina, Andrea (The journal of clinical endocrinology and metabolism, 2015)
Context:GH excess causes an increase in bone turnover, but the consequences in terms of skeletal fragility have long been uncertain due to the heterogeneity of studies dealing with this topic.Objective:We conducted a meta-analysis of studies examining the effects of acromegaly on bone turnover, bone mineral density (BMD), and fractures. Furthermore, we evaluated the effects of sex, gonadal status, and activity of disease on skeletal end-points in acromegaly.Data Sources:We conducted MEDLINE and EMBASE systematic searches up to December 31, 2013.Study Eligibility Criteria:Studies conducted in patients with acromegaly and reporting at least one determinant of skeletal fragility.Data Extraction and Analysis:Study design, patient characteristics, interventions, and outcomes were independently extracted by two authors. We calculated the standardized mean difference (SMD) of bone turnover and BMD differences, whereas fractures were presented as relative frequencies in acromegaly and odds ratios between patients and controls.Results:Forty-one studies fulfilled eligibility criteria and were therefore selected for data extraction and analysis. A total of 1935 patients were included (eight to 206 per study). Acromegaly patients had higher bone formation (SMD, 1.49; 95% confidence interval [CI], 0.97–2.01; P < .0001) and bone resorption (SMD, 1.57; 95% CI, 1.03–2.10; P < .0001) as compared to control subjects, without significant differences in lumbar spine BMD. BMD at the femoral neck tended to be higher in acromegaly patients vs control subjects (SMD, 0.67; 95% CI, 0.07–1.27; P = .03). Patients with acromegaly had high frequency of vertebral fractures (odds ratio, 8.26; 95% CI, 2.91–23.39; P < .0001), in close relationship with male gender, hypogonadism, and active acromegaly.Limitations:Limitations included heterogeneous study protocols with possible variability in the assessment of skeletal end-points.Conclusions:Skeletal fragility is an emerging complication of acromegaly.